Line of investigation 'single-case experimental design in psychotherapy sessions': methodological decisions - Meyer, Sonia Beatriz; Oshiro, Claudia Kami (Perspectivas em Análise do Comportamento, 2019)
The objective is the report of the experience accumulated by the research group Methodologies of research and production of evidence in Behavior Analytic Therapy of the University of São Paulo. Data from 28 studies since 2001 were analyzed in methodological aspects. Were analyzed: Creation of categorization systems or use of existing categorization systems; Units of analysis; Data analysis by frequency, duration and sequential analysis; Experimental, single-case research designs. The behavioral measures of therapists reached stability, allowing a comparison between studies. Measures of client behavior point to the need for individualization, but with models on which to base. The measures are predominantly for behaviors that occur in session. To observe trends of change, several sessions are necessary; three are often insufficient. Data analysis was performed based on frequency of occurrence or duration. Sequential analysis was more informative of therapist-client interactions that might be responsible for changes in psychotherapy. Descriptive studies provided the basis for reaching a research model, the single-case experimental design as a way to produce more conclusive data. This design has been replicated several times.